2016
DOI: 10.3892/ijmm.2016.2478
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of uncoupling protein 2 inhibits the high glucose-induced apoptosis of human umbilical vein endothelial cells

Abstract: Ectopic apoptosis of vascular cells plays a critical role in the early stage development of diabetic retinopathy (DR). Uncoupling protein 2 (UCP2) is a mitochondrial modulator which protects against endothelial dysfunction. However, the role which UCP2 plays in endothelial apoptosis and its association with DR was unclear. In the present study, we investigated whether UCP2 functioned as an inhibitor of DR in endothelial cells. Firstly, we noted that in UCP2-knockout mice retinal cell death and damage in vivo w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Brownlee proposed that mitochondrial production of ROS in response to hyperglycemia may be a key initiating step in the pathogenesis of diabetes, including DR [ 8 ]. Other studies have established a close relation between intracellular ROS production and retinal endothelial cell apoptosis [ 9 , 32 , 33 ]. In our BREC system, we confirmed that HG stimulates ROS production leading to cleaved caspase-3 expression and apoptosis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Brownlee proposed that mitochondrial production of ROS in response to hyperglycemia may be a key initiating step in the pathogenesis of diabetes, including DR [ 8 ]. Other studies have established a close relation between intracellular ROS production and retinal endothelial cell apoptosis [ 9 , 32 , 33 ]. In our BREC system, we confirmed that HG stimulates ROS production leading to cleaved caspase-3 expression and apoptosis.…”
Section: Discussionmentioning
confidence: 93%
“…A hypothesis has been proposed that high blood glucose induces oxidative stress through the generation of excessive reactive oxygen species (ROS), which play a dominant role in the development of chronic complications caused by diabetes, including retinopathy [ 7 , 8 ]. Several studies suggested that HG can lead to overproduction of ROS in endothelial cells and subsequent apoptosis [ 9 ]. Peroxisome proliferator-activated receptor- γ coactivator 1 α (PGC-1 α ) is an important mediator of the metabolic effects of ROS, where PGC-1 α activation results in the increase of mitochondrial energy metabolism and the cellular capacity to detoxify ROS, thereby reprogramming cell metabolism to maintain survival [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A hypothesis has been proposed that high blood glucose induces oxidative stress through the generation of excessive ROS, which play a dominant role in the development of chronic complications caused by diabetes [ 32 , 33 ]. Several studies have suggested that high glucose can lead to the accumulation of ROS in endothelial cells and initiate apoptosis [ 34 ]. Peroxisome proliferator-activated receptor-γ coactivator 1α (PGC-1α) is an important mediator of the metabolic effects of ROS, as PGC-1α activation results in increases in mitochondrial energy metabolism and the cellular capacity to detoxify ROS, thereby reprogramming cell metabolism to maintain survival [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular lesions are the main complications of diabetes and the primary reason for death caused by diabetes [3]. Pathological and physiological changes caused by high glucose such as oxidative stress, activation of sorbitol bypass metabolic abnormalities, and decreased mitochondrial biogenesis, are associated with endothelial dysfunction [4]. Therefore, reducing vessel damage and maintaining endothelial cell function are essential to slow the development of diabetic complications and improve the living quality of diabetes patients.…”
Section: Introductionmentioning
confidence: 99%